Just war and ordered liberty - Miller, Paul D. ca. 20./21. Jh (Cambridge University Press, 2021)
When is war just? What does justice require? If we lack a commonly-accepted understanding of justice - and thus of just war - what answers can we find in the intellectual history of just war? Miller argues that just war thinking should be understood as unfolding in three traditions: the Augustinian, the Westphalian, and the Liberal, each resting on distinct understandings of natural law, justice, and sovereignty. The central ideas of the Augustinian tradition (sovereignty as responsibility for the common good) can and should be recovered and worked into the Liberal tradition, for which human rights serves the same function. In this reconstructed Augustinian Liberal vision, the violent disruption of ordered liberty is the injury in response to which force may be used and war may be justly waged. Justice requires the vindication and restoration of ordered liberty in, through, and after warfare
Literaturverzeichnis Seite 254-262
Abweichender Titel dem Cover entnommen
Enthaltene Kapitel: Thinking about war -- The Augustinian tradition -- The transition -- The Westphalian tradition -- Competing visions of a liberal tradition -- Augustinian liberalism -- Just war and ordered liberty -- Case studies -- Conclusion
Keywords: Just war doctrine; War (Philosophy); War / Moral and ethical aspects; Militärpolitik; Ethik; Militär; Gerechter Krieg; United States / Military policy / 21st century / Case studies; USA